Sex Differences in Depression-Like Behaviors in Adult Mice Depend on Endophenotype and Strain - Pitzer, Claudia; Kurpiers, Barbara; Eltokhi, Ahmed (Frontiers in Behavioral Neuroscience, 2022)
Depression affects women nearly twice as frequently as men. In contrast, rodent models of depression have shown inconsistent results regarding sex bias, often reporting more depression-like symptoms in males. This sex discrepancy in rodents modeling depression may rely on differences in the baseline activity of males and females in depression-related behavioral tests. We previously showed that the baseline despair and anhedonia behaviors, major endophenotypes of depression, are not sex biased in young adolescent mice of C57BL/6N, DBA/2 and FVB/N inbred wild-type strains. Since the prevalence of depression in women peaks in their reproductive years, we here investigated sex differences of the baseline depression-like behaviors in adult mice using these three strains. Similar to the results in young mice, no difference was found between adult male and female mice in behavioral tests measuring despair in both tail suspension and forced swim tests, and anhedonia in the sucrose preference test. We then extended our study and tested apathy, another endophenotype of depression, using the splash test. Adult male and female mice showed significantly different results in the baseline apathy-like behaviors depending on the investigated strain. This study dissects the complex sex effects of different depression endophenotypes, stresses the importance of considering strain, and puts forward a hypothesis of the inconsistency of results between different laboratories investigating rodent models of depression.